Enterprise Java 2, J2EE 1.3 complete (SYBEX, 2002)
With Enterprise Java 2, J2EE 1.3 Complete, you'll learn everything you need to know for developing large-scale web and network applications with Java. You'll begin by learning which components combine to form the enterprise platform, and then move on to basic development skills: Servlet programming, creating JavaServer Pages, and programming JavaBeans. You'll also learn database programming concepts and skills, and how to secure your network from malevolent intruders. You'll learn to use XML and its related technologies for seamless cross-platform data exchange. Finally, you'll learn advanced JavaBeans programming to create reusable software components. As a bonus, the last part of the book teaches you to program spiders and bots: Although not a part of J2EE, it's a fun topic that can come in handy for Internet developers who want to create agents to automatically retrieve and organize web content.